Nodular fasciitis causing unilateral proptosis. - Perry, R H (1975)
A case report of an unusual case of nodular fasciitis in the orbit presenting with unilateral proptosis is described, and the radiological features are outlined. The histological features are discussed and the benign nature of the lesion stressed. Nodular fasciitis arising in the orbit and presenting as unilateral proptosis has not previously been reported in the literature.